The relationship between person-organization fit, organizational identification and work outcomes - Demir, Mahmut; Demir, Sirvan Sen; Nield, Kevin (Journal of Business Economics and Management, 2014)
The purpose of this research is to analyse the relationship of person-organization fit in hotels through organizational identification, job performance, production deviance behavior, and the intention to remain. To achieve this, first the literature was consulted to provide a conceptual model. Through conducting a face-to-face interview, a total of 582 questionnaires were collected from employees who were full-time employees of the five-star hotels operating within the Mugla region of Turkey. The data obtained from the survey was analysed via the statistics program; within this explanatory and confirmatory factor analyses were performed within the framework of Structural Equation Modelling. The study concluded and identified, that external factors, namely “person-organization fit”, have an effect on internal factors such as “organizational identification”, “job performance”, “production deviance” and the “intention to remain”. The empirical results indicate that person-organization fit has a significant and positive influence on organizational identification, job performance and intention to remain, while has a significant and negative influence on production deviance behavior. The results also indicate that the organizational identification has an important effect on job performance, intention to remain and production deviance behavior.